Developing FlARe: A Chemi-Genetic Maleimide-Based Approach to Fluorogenic Protein Labelling - Tsao, Kelvin Ka-Wai (Université d'Ottawa / University of Ottawa, 2020)
Studying protein expression, localization, and behaviour within cells is invaluable to understanding biological processes. Fluorescent protein labelling can be used to easily visualize these biomolecules. However, many strategies use large fluorescent proteins or enzyme tags that disrupt the native localization and conformation of proteins of interest. FlARe is a minimalistic, chemi-genetic fluorogenic protein labelling method with two components, the FlARe probe and the dC10 tag. The probe consists of a fluorophore linked to two maleimides, which quench the fluorophore’s emission. They also react with the complementary dC10 peptide tag that is genetically fused to a specific protein and contains two cysteines positioned 10 Å apart. Reaction with dC10 anchors the FlARe probe to the tagged protein and abolishes the maleimides’ quenching mechanisms. This releases the probe’s intrinsic fluorescence, allowing the protein to be visualized by fluorescence. This thesis sets out to complete three objectives: 1) To improve the FlARe probe chemical structure; 2) To implement novel developments of the FlARe protein labelling technique into live mammalian cells; 3) To expand the scope of the FlARe method to include bioconjugation. To make the current FlARe probe design more stable in the aqueous milieu of the cell, a new FlARe probe, KT12, was synthesized. This new probe was more stable than the current YC20 FlARe probe but not more selective. Despite this, valuable insight was made into the mechanisms of maleimide hydrolysis and thiol addition. After establishing that the current methoxymaleimide FlARe probe offered the most selective design, we invested our efforts into implementing the FlARe labelling technique in live mammalian cells. To this end, a recombinant protein carrying different variants of the dC10 tag was successfully labelled with FlARe probes emitting at different wavelengths. Finally, we blended our expertise in probe design and biological implementation to develop a novel fluorogenic linker to form bioconjugates. As a result, a FlARe linker functionalized with both the dimaleimide moiety and an alkyne linker was designed. The successful synthesis and proof-of-principle demonstration of this novel FlARe linker were performed, allowing for the modular formation of fluorogenic bioconjugates. These developments to FlARe advance this minimalistic and fluorogenic protein imaging method. This improves the current capability to fluorescently label proteins in cells in a non-disruptive manner. Thus, complex questions surrounding cell biology can be answered to better understand biological processes.
Keywords: Labelling; Fluorescence; Chemistry; Synthesis; Chemical_Biology